2021
DOI: 10.1021/acs.energyfuels.1c02152
|View full text |Cite
|
Sign up to set email alerts
|

Powerful Synergy of Acetylenic Diol Surfactants with Kinetic Hydrate Inhibitor Polymers—Choosing the Correct Synergist Aqueous Solubility

Abstract: The performance of injected kinetic hydrate inhibitor (KHI) polymer solutions can be boosted considerably by judicious choice of the polymer solvent system. We report the excellent KHI synergism of the low-foaming acetylenic diol gemini surfactant 2,4,7,9-tetramethyl-5-decyne-4,7-diol (TMDD) with poly(N-vinyl caprolactam), N-vinyl caprolactam:N-vinyl pyrrolidone copolymer, and poly(N-isopropylmethacrylamide). Highpressure rocking cell tests, using the slow constant cooling method or the isothermal method, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“… 38 Also, 1 mL of decane was added to the cells, and the subcooling temperature was approximately 15.5 °C. 39 …”
Section: Resultsmentioning
confidence: 99%
“… 38 Also, 1 mL of decane was added to the cells, and the subcooling temperature was approximately 15.5 °C. 39 …”
Section: Resultsmentioning
confidence: 99%
“…The decane has two main effects. First, it lowers the equilibrium temperature, in this case by about 0.3 °C . Second, it can become a solvent for the KHI formulation, in particular, iHexOl, in this study.…”
Section: Resultsmentioning
confidence: 73%
“…Some salinity is often present even in gas lines, so we wanted to explore the effect of added 0.5 wt % NaCl. Earlier work had suggested that sparingly soluble solvent synergists might lose their activity if they partition to the liquid hydrocarbon phase . Therefore, we were interested in confirming this claim using iHexOl, which has limited water solubility, and TBGE, which is very water-soluble and not expected to partition to the hydrocarbon phase.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations